Sindrom Rett: Kelainan Genetik Penyebab Disabilitas Intelektual - Nisa Ihsani; Elisca Nurhayati; Tabina Khalishah Dzikra Dzakirah; Yesi Repani (Jurnal Biodiversitas dan Bioteknologi, 2024)
Rett Syndrome (RTT) is a rare genetic disorder affecting early neurological development that has a mutation linked to the X chromosome in the MECP2 gene that codes for methyl CpG-binding protein 2, resulting in loss of function. Typical symptoms of Rett Syndrome are impaired communication and loss of speech, loss of hand use, repetitive, involuntary hand movements such as hand washing, loss of mobility, or difficulty walking. Rett Syndrome is very rare in Indonesia. It occurs in 1 in 10,000 - 15,000 children. A specific treatment cannot treat Rett Syndrome. However, treatment can be done for the symptoms, including sleep disorders, eating disorders, seizures, and self-injurious behavior. Trefinetide is one treatment that is specific to the main symptoms of Rett Syndrome.